Joint modelling and simulation of M‐protein dynamics and progression‐free survival for alternative isatuximab dosing with pomalidomide/dexamethasone. Issue 5 (26th November 2021) - Thai, Hoai‐Thu; Gaudel, Nadia; Cerou, Marc; Ayral, Geraldine; Fau, Jean‐Baptiste; Sebastien, Bernard; van de Velde, Helgi; Semiond, Dorothée; Veyrat‐Follet, Christine
Abstract : Aims: Addition of isatuximab (Isa) to pomalidomide/dexamethasone (Pd) significantly improved progression‐free survival (PFS) in patients with relapsed/refractory multiple myeloma (RRMM). We aimed to characterize the relationship between serum M‐protein kinetics and PFS in the phase 3 ICARIA‐MM trial (NCT02990338), and to evaluate an alternative dosing regimen of Isa by simulation. Methods: Data from the ICARIA‐MM trial comparing Isa 10 mg/kg weekly for 4 weeks then every 2 weeks (QW‐Q2W) in combination with Pd versus Pd in 256 evaluable RRMM patients were used. A joint model of serum M‐protein dynamics and PFS was developed. Trial simulations were then performed to evaluate whether efficacy is maintained after switching to a monthly dosing regimen. Results: The model identified instantaneous changes (slope) in serum M‐protein as the best on‐treatment predictor for PFS and baseline patient characteristics impacting serum M‐protein kinetics (albumin and β2‐microglobulin on baseline levels, non‐IgG type on growth rate) and PFS (presence of plasmacytomas). Trial simulations demonstrated that switching to a monthly Isa regimen at 6 months would shorten median PFS by 2.3 weeks and induce 42.3% patients to progress earlier. Conclusions: Trial simulations supported selection of the approved Isa 10 mg/kg QW‐Q2W regimen and showed that switching to a monthly regimen after 6 months may reduce clinical benefit in the overall population. However, patients with good prognostic characteristics and with a stable, very good partial response may switch to a monthly regimen after 6 months without compromising the risk of disease progression. This hypothesis will be tested in a prospective clinical trial.